Models of professional career of the managerial women (2013)
In recent years the professional trajectory of women and their access to management positions has earned relevance in the literary corpus. The aim of this work is to describe the professional trajectories that characterize the evolution towards management. The study is based on a series of open-ended, semi-structured interviews that were subjected to a systematic, interpretive analysis using a phenomenological, longitudinal approach. The analysis perspective is based on life stories, by means of a declaration or story about the last 12 years of nine women's careers. These stories reveal the events, lived and told, which characterize the professional trajectory where they occur. The results show 4 career models as a way of analyzing the professional trajectories.